Contingency Perspectives of Organizational Strategy: A Critical Review of the Empirical Research - Ginsberg, Ari; Venkatraman, N. (Academy of Management Review, 1985)
Ari Ginsberg, N. Venkatraman, Contingency Perspectives of Organizational Strategy: A Critical Review of the Empirical Research, The Academy of Management Review, Vol. 10, No. 3 (Jul., 1985), pp. 421-434